Epithelial deletion of podoplanin is dispensable for re‐epithelialization of skin wounds. Issue 10 (October 2015) - Baars, Sebastian; Bauer, Christine; Szabowski, Sibylle; Hartenstein, Bettina; Angel, Peter
Abstract The mucin‐like transmembrane protein podoplanin (PDPN) is prominently represented in tumor‐associated gene expression signatures of numerous types of cancer including squamous cell carcinoma, and gain‐of‐function and knockdown approaches in tissue culture strongly suggested an important role of PDPN in cell proliferation, migration and adhesion. PDPN is absent during epidermal homeostasis but is highly expressed in basal keratinocytes during cutaneous wound healing. Enhanced motility of immortalized keratinocytes upon ectopic PDPN overexpression argues for wound healing defects upon podoplanin deficiency in keratinocytes; however, in vivo data that unequivocally define the impact of PDPN by functional studies in a physiologically relevant system are still missing. Here, we have applied an in vivo loss‐of‐function approach by generating a novel transgenic mouse line with keratinocyte‐specific podoplanin deficiency. Performing cutaneous full‐thickness excisional wounds to examine re‐epithelialization capacity, unexpectedly, no defects were observed in wound healing properties of mutant mice. Similarly, PDPN‐deficient primary keratinocytes showed no impairment in migration, adhesion or proliferation. Thus, PDPN function is not rate‐limiting for re‐epithelialization but may be functionally compensated by an as yet unknown protein. Our data also call for in vivo functional studies on PDPN in settings of skin tumor development and progression to clarify PDPN's role in skin pathology.